Phosphate Solubilisation Index and Antagonism Potential of Frangipani Tree Rhizosphere Bacterial Isolates from Cemetery - Febriyanti, Vika; Tyastuti, Erma Musbita; Sidiq, Yasir; Rahayu, Triastuti (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Frangipani trees (Plumeria acuminata) are commonly found in cemeteries. Cemeteries are used as a location for interment so that the corpse actively decomposes to provide soil minerals that encourage the formation of microbes, including bacteria. Bacteria around the roots of frangipani trees are thought to have potential as plant growth-promoting rhizobacteria (PGPR). Based on reference searches, there has been no research on frangipani tree rhizosphere bacteria from burial grounds. The aim of this study was to investigate the phosphate-dissolving and blast disease-causing Pyricularia oryzae fungus-inhibiting properties of frangipani tree rhizosphere bacteria from Pracimaloyo cemetery, Surakarta. A total of 39 isolates of frangipani tree rhizosphere bacteria were tested for their ability to dissolve phosphates using PKA media (Pikovskaya), while the antagonism test against the fungal pathogen Pyricularia oryzae used the dual assay method. The results of the study showed that 15% of the rhizosphere bacteria of the frangipani tree were able to dissolve phosphate, and 33% of the isolates were able to inhibit the growth of the fungus Pyricularia oryzae with an inhibitory power of more than 40%. Based on the results, the rhizosphere bacterial isolates from Pracimaloyo TPU show the characteristics of a possible PGPR.